Similarities and Differences Between Two Deadly Caribbean Coral Diseases: White Plague and Stony Coral Tissue Loss Disease - Cróquer, Aldo; Weil, Ernesto; Rogers, Caroline S. (Frontiers in Marine Science, 2021)
For several decades white plague (WPD) and more recently, stony coral tissue loss disease (STCLD) have significantly impacted Caribbean corals. These diseases are often difficult to separate in the field as they produce similar gross signs in their hosts. Here we aimed to compare what we know about WPD and SCTLD in terms of: (1) pathology, (2) etiology and (3) epizootiology. We reviewed over 100 peer-reviewed publications from 1973 to 2021 in google scholar, web of science, pubMed and Scopus. Overall, WPD and SCTLD may resemble each other macroscopically, because of the rapid tissue loss they produce in their hosts. However, multiple-coalescent lesions are often observed in colonies with SCTLD and rarely in WPD. A clearer diagnostic sign of SCTLD is the frequent presence of a bleaching front between the apparently healthy tissues and the recently exposed coral skeleton. Bleached circular areas seem to be present when SCTLD is first appearing on the colony, a feature that is absent in WPD. The paucity of histopathologic studies hampers comparisons of changes produced by WPD and SCTLD at the tissue level. Both diseases alter the coral microbiome. WPD is controversially regarded as a bacterial infection and more recently a viral infection, whereas for SCTLD the etiology has not been identified, but the disease is believed to target the zooxanthellae. Most striking differences between WPD and SCTLD have been related to duration and phases of epizootic events and mortality rates. While both diseases may become highly prevalent on reefs, SCTLD seems to be more persistent even throughout years. Both transmit horizontally and directly with water-borne and/or organism-mediated transmission. Given the differences and similarities between these diseases, more detailed information is needed for a better comparison. Specifically, it is important to focus on: (1) tagging colonies to look at disease partial and/or complete mortality rates , (2) tracking the fate of the epizootic event by looking at initial coral species infected, the features of lesions and how they spread to a wider range of hosts, (3) persistence across years and (4) repetitive sampling to look at changes in the microbiome as the disease progresses.